The Integrated Environmental Permit: Requirements of EU Legislation, Practice of its Implementation in Poland, Prospects for Ukraine - Nadiya Kobetska (Vasyl Stefanyk Precarpathian National University, 2018)
The article is aimed at analyzing the system of integrated environmental permit regulation. It includes a study of Directive 2010/75/EU analyzing the specific features, requirements, grounds of and the procedure for issuance of integrated permits. Since the Directive is a framework document, each state makes its own decisions as to what mechanisms to use. The article studies the statutory regulation and the practice of the implementation of integrated permits in the neighbouring Poland. It interprets the principal legal environmental document of the Republic of Poland - the Environmental Protection Act. Its main focus is on defining the conditions for the application of the BAT principle and the procedure for permit issuance: the competent authorities, time limits, control, etc. Ukrainian legislation on permits for emissions of pollutants into ambient air, discharges into waters, and waste management is subject to independent analysis. On the basis of the study, the generalized characteristic features of the integrated permit system in the sphere of environmental protection and environmental safety enforcement, the principal tasks and measures aimed at ensuring the implementation of the system of integrated environmental permits in Ukraine are defined.